2007
DOI: 10.1177/0961203307084160
|View full text |Cite
|
Sign up to set email alerts
|

Sensorineural dysacusis in patients with systemic lupus erythematosus

Abstract: The objective of this study was to establish the frequency of involvement of the auditory apparatus in 45 female patients with systemic lupus erythematosus (SLE) submitted to general clinical and laboratory assessments, and tone and vocal audiometry accompanied by a questionnaire evaluating auditory symptoms. The control group consisted of 45 healthy women, matched by age. Auditory symptoms were present in 25 (55.5%) patients, with a diagnosis of sensorineural hearing loss in seven (15.6%) patients. A signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 16 publications
1
20
0
4
Order By: Relevance
“…This result agrees with those of other studies which found no correlation between hearing threshold and age, organ system involvement, SLE duration or SLE severity. 1,4,12,16,17,20 However, this may be due to the Our study patients were enrolled at a younger age than those of previously reported studies; however, at 10-year follow up our patients' mean age was similar to that of patients reported earlier (Table III). Considering the age of our patients, it would be reasonable to exclude the effect of some inner ear disorders, such as age-related hearing loss (presbycusis) and long-term exposure to environmental noise (e.g.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…This result agrees with those of other studies which found no correlation between hearing threshold and age, organ system involvement, SLE duration or SLE severity. 1,4,12,16,17,20 However, this may be due to the Our study patients were enrolled at a younger age than those of previously reported studies; however, at 10-year follow up our patients' mean age was similar to that of patients reported earlier (Table III). Considering the age of our patients, it would be reasonable to exclude the effect of some inner ear disorders, such as age-related hearing loss (presbycusis) and long-term exposure to environmental noise (e.g.…”
Section: Discussionmentioning
confidence: 49%
“…However, an increased prevalence of subclinical or slowly progressive SNHL has been reported in SLE patients. [16][17][18] Based on their audiometric studies, Roverano et al 4 have recommended that audiometric tests be included as part of initial studies in patients with systemic lupus disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Subclinical SNhl in rheumatic diseases an increased prevalence of subclinical or slowly progres sive snHl has been reported in patients with ra, sjögren's syndrome, sle, wG and systemic sclero sis. 27,42,43 no correlation has been observed with disease activity. the disease mechanism and implications for therapy outside of acute or rapidly progressive symptoms are uncertain.…”
Section: Snhl In Other Clinical Contextsmentioning
confidence: 98%
“…Apabila vaskulitis terdapat pada arteri labirin dan cabangnya pada penderita LES, keadaan tersebut mengakibatkan gangguan pada pendengaran. [3][4][5] Kerusakan telinga pada pasien LES sudah banyak dilaporkan. Pada penelitian di Polandia pada tahun 2009 terhadap 35 pasien LES, dari pemeriksaan brainstem evoked respons auditory (BERA) didapatkan bahwa 10 orang mengalami gangguan dengar sensorineural secara simetris pada frekuensi tinggi.…”
Section: Pendahuluanunclassified